PERAN TAYANGAN ADIT SOPO JARWO (ASJ) TERHADAP PENDIDIKAN KARAKTER ANAK SEKOLAH DASAR DI KABUPATEN KUTAI KARTANEGARA - Nur Agus Salim (PENDAS MAHAKAM: Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2017)
Television is a mass media that has the ability to access information quickly and reach audiences in infinite numbers from children to adults. Television with a variety of channels with various events that aired has been able to attract the audience, and make the audience interested because it is presented with an attractive appearance and settings tailored to the needs of the audience. Based on this study was prepared with the aim to determine the effect that can be caused by animated impressions Adit Sopo Jarwo. Adit Sopo Jarwo is a work of the nation that deserves an appreciation so it is necessary to get special attention whether the show that aired has a positive impact on the audience, especially the children who generally love to watch cartoons. The method used is qualitative to determine how to find, collect, process and analyze data of research result. Based on the result of the research, it is concluded that the character education value of Adit Sopo Jarwo show is that children begin to learn to be a small realist who eagerly learns and controls the world objectively. Children observe objects and some people more closely, memorize and memorize strengthen , Learning to hang out with peers, developing conscience, moral understanding, and values, developing the necessary concepts daily and liking pictorial stories.